2023
DOI: 10.1101/2023.03.24.534081
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ferroptosis propagates to neighboring cells via cell-cell contacts

Abstract: Ferroptosis is an iron-dependent form of regulated cell death characterized by accumulation of peroxidized lipids and plasma membrane disruption, whose molecular mechanism of execution remains poorly understood. Here, we developed a new optogenetic system, Opto-GPX4Deg, for light-induced degradation of the lipid reducing protein GPX4, which allows controlled ferroptosis induction with high precision in time and space. By using Opto-GPX4Deg to study cell death dynamics within the cellular population, we found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…The formed truncated PLs, which are known to permeabilize lipid membranes (23)(24)(25)(26), are promising candidates to cause loss of membrane integrity and mediate ferroptotic membrane permeabilization (27). Consistent with this model, during late-stage ferroptosis, it has been reported that plasma membrane pores form leading to cell swelling, calcium influx and recruitment of membrane repair machinery (28)(29)(30)(31). potassium (Na + /K + )-ATPase were identified as critical steps contributing to loss of the plasma membrane cation gradient (32).…”
Section: Introductionmentioning
confidence: 71%
“…The formed truncated PLs, which are known to permeabilize lipid membranes (23)(24)(25)(26), are promising candidates to cause loss of membrane integrity and mediate ferroptotic membrane permeabilization (27). Consistent with this model, during late-stage ferroptosis, it has been reported that plasma membrane pores form leading to cell swelling, calcium influx and recruitment of membrane repair machinery (28)(29)(30)(31). potassium (Na + /K + )-ATPase were identified as critical steps contributing to loss of the plasma membrane cation gradient (32).…”
Section: Introductionmentioning
confidence: 71%